Gamma Radiation‐Induced Degradation of Acetohydroxamic Acid (AHA) in Aqueous Nitrate and Nitric Acid Solutions Evaluated by Multiscale Modelling. Issue 5 (5th December 2022) - Conrad, Jacy K.; Mezyk, Stephen P.; Isherwood, Liam H.; Baidak, Aliaksandr; Pilgrim, Corey D.; Whittaker, Daniel; Orr, Robin M.; Pimblott, Simon M.; Horne, Gregory P.
Abstract: Acetohydroxamic acid (AHA) has been proposed for inclusion in advanced, single‐cycle, used nuclear fuel reprocessing solvent systems for the reduction and complexation of plutonium and neptunium ions. For this application, a detailed description of the fundamental degradation of AHA in dilute aqueous nitric acid is required. To this end, we present a comprehensive, multiscale computer model for the coupled radiolytic and hydrolytic degradation of AHA in aqueous sodium nitrate and nitric acid solutions. Rate coefficients for the reactions of AHA and hydroxylamine (HA) with the oxidizing nitrate radical were measured for the first time using electron pulse radiolysis and used as inputs for the kinetic model. The computer model results are validated by comparison to experimental data from steady‐state gamma ray irradiations, for which the agreement is excellent. The presented model accurately predicts the yields of the major degradation products of AHA: acetic acid, HA, nitrous oxide, and molecular hydrogen. Abstract : The fundamental reaction pathways for the radical‐induced degradation of acetohydroxamic acid in aqueous solutions of sodium nitrate and nitric acid are studied and simulated by a comprehensive multiscale computer model. The model predictions show excellent agreement with the time‐resolved and steady‐state experimental irradiation data newly measured in this work.